Efecto de la escarificación y la dosis del ácido giberélico (ag3) en la germinación de semilla de curuba (passiflora mollisima) (1988)
The trials made on banana passion fruit seeds germination (Passiflora mollisima(HBK) Bailey, under laboratory specifications show that the testa delays the water absortion and it is the critic factor on the germination. AG3 increases the germination remarkably and strengthens the effects of the scarification considerably.